Little house on the prairie - Wilder, Laura Ingalls, 1867-1957 (Wilder, Laura Ingalls, 1867-1957. Little house books., 1953)
A family travels from the big woods of Wisconsin to a new home on the prairie, where they build a house, meet neighboring Indians, build a well, and fight a prairie fire.